2009
DOI: 10.1380/ejssnt.2009.530
|View full text |Cite
|
Sign up to set email alerts
|

Proton Conductivity of Oligomeric Poly[(1,2-Propanediamine)-alt-(Oxalic Acid) Thin Films on Al2O3 Substrates

Abstract: Proton transport properties of three thin films (110, 240, and 360 nm thick films) on R-plane (1102) sapphire substrates for oligomeric poly[(1, 2-propanediamine)-alt-(oxalic acid)] were investigated. The maximum proton conductivity of the thin film is 1.7 × 10 −3 S cm −1 at the RH of 80%, which is five times higher than that of the bulk sample (3.0 × 10 −4 S cm −1 ). The activation energies of the 110, 240, and 360 nm thick films are found to 0.74, 0.67, and 0.68 eV at the RH of 80%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Figure 4c shows that the substrate dependence of the proton conductivity was observed in the amide thin films. 26,99 The amide thin films showed different proton conductivity on SiO 2 , R-plane sapphire, and MgO (100). The proton conductivity varied from 4 × 10 −3 to 1 × 10 −4 S cm −1 under the same conditions of 80% RH and 298 K. This difference in the proton conductivity is probably attributable to the difference in the interfacial structure.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Figure 4c shows that the substrate dependence of the proton conductivity was observed in the amide thin films. 26,99 The amide thin films showed different proton conductivity on SiO 2 , R-plane sapphire, and MgO (100). The proton conductivity varied from 4 × 10 −3 to 1 × 10 −4 S cm −1 under the same conditions of 80% RH and 298 K. This difference in the proton conductivity is probably attributable to the difference in the interfacial structure.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Results showed that proton conductivity is changed by molecular orientation of the polymer according to an interaction between the substrate and the polymer interface [21,22]. In 2008, the first report was made of a study in which the proton conductivity of oligo[(1,2-propanediamine)-alt-(oxalic acid)] thin films was improved by the molecular orientation [23][24][25]. As the oriented structure of other research groups, Tamura and Kawakami presented composite membranes containing uniaxially aligned sulfonated polyimide nanofibers by an electrospinning process (Figure 1(f)) [26].…”
Section: Introductionmentioning
confidence: 99%
“…They found that ion domains flattened along the in-plane direction and ordered along the thickness direction from the results of small angle X-ray scattering measurements. Recently, anomalous proton conductivity through the synthesis of thin films of proton-conductive oligomeric amides and polypeptide has been reported [2][3][4][5]. These proton conductivities are dependent on the thickness of the thin film, and the maximum proton conductivity of the thin film exhibits a value 10 times higher than that of the pelletized sample.…”
Section: Introductionmentioning
confidence: 99%